A review of thermodynamics and heat transfer in solar refrigeration system - Afshar, O.; Saidur, Rahman; Hasanuzzaman, M.; Jameel, M. (Elsevier, 2012)
Solar energy is one of the most efficient, clean and affordable energy alternatives available today. With the current concerns about global warming and ever increasing energy rates, countries are seriously looking for domestic and industrial usage of solar energy. In the present study, a detail review of the application of solar energy for refrigeration systems has been carried out. The utilization of solar energy for refrigeration systems would help in improvement of energy economics, energy consumption and energy efficiency. The review focuses especially on solar panel, desiccant fluid for icemaker and its components. The study also includes thermodynamic equation and material for making component of refrigeration to improve the coefficient of performance. Study around the economic evaluation and solar performance coefficient in the type of refrigerator, modeling and simulation, mathematical equation of heat transfer and type of absorption used are other topics that could be considered.